Accreditation soccer fields with artificial turf: guarantee of success - Gallardo, Leonor; Sánchez Sánchez, J.; Gallardo, Ana; Felipe, José Luis; Burillo, P. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2013)
In recent decades, artificial turf is undergoing constant evolution, not only in quality but also in the quality of its structural components. This growth has created the need to know the artificial pavement conditions in relation to a predetermined quality standards, emerging different regulations based on the purpose and status of the surface. There are currently three different approval systems for such surfaces. On the one hand, the UNE-EN 15330-1:2007, which is specific for artificial turf surfaces for outside use, more oriented to community sports, recreation and education, and secondly, those that are more related with the high athletic performance, such as FIFA certification (1 and 2 stars), which is international, and the RFEF Mark of Quality (level 1 and 2) which is national. The implementation of these accreditations ensures the quality of the pavement, improving performance and placing it at the level of the natural grass.